2017
DOI: 10.3389/fphys.2017.00801
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Risk Factors for High-Altitude Headache in Chinese Men Following Acute Exposure at 3,700 m

Abstract: Background: High-altitude headache (HAH) is a notably common disorder affecting the daily life of travelers ascending to high altitude. Hematological parameters are important clinical examinations for various diseases. Today, hematological characteristics of HAH remain unrevealed. Above all, we aimed to ascertain hematological characteristics and independent risk factors/predictors associated with HAH before and after exposure at 3,700 m.Methods: Forty five healthy men were enrolled in present study. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…In addition, within hours of exposure to high altitude hypoxia, hypoxic tachypnea may lead to respiratory alkalosis, increased natriuresis and diuresis, promoting fluid shift away from intravascular space, result in blood concentration, even hypovolemia [ 21 ]. Our study observed most hematological parameters (RBC, Hgb, Hct, MCH, PLT, WBC and LYM#) were elevated from sea-level to altitude of 3700 m within a 72 h ascending processes, which also in consistency with previous studies [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, within hours of exposure to high altitude hypoxia, hypoxic tachypnea may lead to respiratory alkalosis, increased natriuresis and diuresis, promoting fluid shift away from intravascular space, result in blood concentration, even hypovolemia [ 21 ]. Our study observed most hematological parameters (RBC, Hgb, Hct, MCH, PLT, WBC and LYM#) were elevated from sea-level to altitude of 3700 m within a 72 h ascending processes, which also in consistency with previous studies [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated that young age, smoking history, higher body mass index history of migraine, high heart rate (HR) and low pulse oxygen saturation (SpO 2 ) are independent risk factors for HAH [ 1 , 11 13 ]. Previously, Huang et al performed the first investigation on the relationship between hematological parameters and HAH before and after rapid ascending at 3700 m with 45 subjects, and found that HAH is associated with sea-level reticulocyte and neutrophil counts [ 14 ]. Because erythrocytes are the principal carrier of oxygen in the circulatory system, the hematological parameters may provide useful information regarding HAH.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the sample number at 95% confidence interval, 80% chance of detection and ratio of wild type to homozygous haplotype carrying individuals being set at 0.2 for high altitude given 80% of the Tibetans carry this haplotype at high altitude and 50% of Tibetans carry this haplotype at sea level [ 10 , 16 ]. Based on available literature [ 34 , 35 ] addressing WBC and monocyte percentage alteration as a result of hypobaric hypoxia exposure we set a difference of 5% between means of the two genotypes and a standard deviation of 5. The calculation was done using CDC's statistics tool ( http://www.openepi.com/Menu/OE_Menu.htm ) The prediction of the sample size calculation was to collect 48 PHD2 D4E;C127S homozygous individuals and 10 PHD2 WT individuals from high altitude and 16 PHD2 D4E;C127S homozygous and 16 PHD2 WT individuals from sea-level.…”
Section: Methodsmentioning
confidence: 99%
“…The CIBERSORT predictions also suggested that the expression profile of white blood cells exhibited inconsistencies. This result committed to the study at 3700 m demonstrated an increase in neutrophils and a slight decrease in lymphocytes [ 29 ] and exposure to acute hypoxia marginally raised the neutrophils [ 30 ]. However, several investigations revealed contradictory results.…”
Section: Discussionmentioning
confidence: 87%